Molecular docking of ferulic acid, bakuchiol and niazirin on peroxisome proliferator-activated receptor gamma (PPAR-γ) as anti-diabetic agents - Anjar Hermadi Saputro; Riri Fauziyya; Sarmoko; Iwan Syahjoko Saputra (Indonesian Society for Biochemistry and Molecular Biology, 2024)
Background: Diabetes mellitus remains one of the most dangerous illnesses worldwide. The PPAR-gamma protein plays a crucial role in lipid and carbohydrate metabolism, making it a key target for diabetes therapy. Research into plant-derived active compounds for diabetes treatment is increasingly important. Objective: This study aims to evaluate and analyze the interaction of ferulic acid, niazirin, and bakuchiol with the peroxisome proliferator-activated receptor gamma (PPAR-γ) protein using molecular docking. Methods: Molecular docking was employed to assess the interactions between ferulic acid, niazirin, bakuchiol, and the PPAR-γ protein (PDB ID: 2PRG). The analysis focused on binding free energy values, amino acid residue interactions, the number of hydrogen bonds, and bond distances, comparing these results to those of the native ligand and pioglitazone, a known anti-diabetic drug targeting PPAR-γ. Results: The binding free energies for the ferulic acid-PPAR-γ, bakuchiol-PPAR-γ, niazirin-PPAR-γ, native ligand-PPAR-γ, and pioglitazone-PPAR-γ complexes were -5.54 kcal/mol, -8.47 kcal/mol, -6.56 kcal/mol, -10.08 kcal/mol, and -9.94 kcal/mol, respectively. The amino acid residue similarity percentages with the native ligand were 18.18% for ferulic acid, 27.27% for bakuchiol, 18.18% for niazirin, and 81.82% for pioglitazone. The native ligand-2PRG and pioglitazone-2PRG complexes exhibited superior hydrogen bond numbers and shorter bond distances compared to the other compounds. Conclusion: Although bakuchiol showed the most promising interaction among the tested compounds, none surpassed the binding affinity and stability of the native ligand or pioglitazone. Further research is needed to optimize these compounds for potential anti-diabetic therapy.